Zero-dripping flame-retardant flexible cable and preparation method thereof

By using aluminum hydroxide, magnesium hydroxide and other components in the cable to prepare zero-drop flame retardant sheath material, combined with flexible sheath and flame retardant mineral filling, the problem of cable falling off and poor mechanical properties during fire is solved. It realizes a cable design that combines high-efficiency flame retardant and softness, meeting the B1-level flame retardant requirements and improving safety.

CN119192716APending Publication Date: 2024-12-27ZHONGTIAN TECH IND WIRE&CABLE SYST CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411313113.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing flame retardant cables are prone to fall off during fire, resulting in the expansion of fire. The mechanical properties of traditional flame retardant sheath materials are poor, making it difficult to ensure the laying of cables in narrow places and prevent the spread of fire.

Method used

Components based on weight percentage include aluminum hydroxide, magnesium hydroxide, ethylene-methacrylic acid, hindered phenol antioxidants, sepiolite, etc., and prepare zero-drip flame retardant through stirring, kneading, extrusion granulation processes. Sheath material and a multi-wire twisted flexible sheath formed on the outer layer of the cable, combined with flame retardant mineral material to ensure that the cable does not fall off during fire and has excellent flame retardant performance.

Benefits of technology

It realizes that the cable does not fall off during fire, prevents the fire from expanding, improves the flexibility and flame retardant performance of the sheath, ensures the strength and stability of the carbon shell at high temperatures, avoids material falling off and fire spread, and meets the B1 flame retardant level. It requires that it does not contain toxic substances, which improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192716A_ABST
    Figure CN119192716A_ABST
Patent Text Reader

Abstract

The invention relates to a zero-dripping flame-retardant flexible cable and a preparation method thereof. The zero-dripping flame-retardant sheath material comprises the following components in percentage by weight: 10%-30% of EVA (Ethylene Vinyl Acetate), 1%-10% of POE (Polyolefin Elastomer), 1%-10% of LLDPE (Linear Low Density Polyethylene), 1%-10% of HDPE (High-Density Polyethylene), 1%-10% of a compatilizer, 0.1%-0.5% of an antioxidant, 20%-50% of an inorganic flame retardant, 0.2%-1% of carbon black, 0.5%-1% of silicone, 0.15%-0.5% of EBS (Ethylene Butylene Styrene), 0.01%-0.6% of TAIC (Triallyl The inorganic flame retardant comprises 10%-40% of magnesium hydroxide and 10%-40% of aluminum hydroxide, ethylene-methacrylic acid is selected as the compatilizer, a hindered phenol type antioxidant is selected as the antioxidant, and sepiolite is selected as the charring agent. The flame-retardant sheath prepared from the zero-dripping flame-retardant sheath material designed by the invention has excellent mechanical property and flame-retardant property, good flame-retardant effect, high carbon shell strength after combustion and no dripping phenomenon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, and in particular to a zero-drip flame-retardant flexible cable and a preparation method thereof. Background Art

[0002] Flame-retardant cables refer to cables whose flames spread only within a limited range after the fire source is removed, and the residual flames or residual burnings extinguish themselves within a limited time. Due to the large differences in the flame retardancy of low-smoke halogen-free polyolefin materials with different performances, the performance of cables such as smoke toxicity, dripping, and heat release varies greatly. Internationally, the EU EN 13501-6 "Fire protection classification of building products and buildings-Part 6: Classification of cable protection test data" standard divides the flame retardant performance of cables into seven levels: Aca, B1ca, B2ca, Cca, Dca, Eca, and Fca, based on multiple indicators such as the calorific value of combustion, flame spread, peak heat release rate, and combustion growth rate index of cable products. In addition, on this basis, additional performance levels are identified based on the three indicators of burning dripping / particles (d), smoke generation level (s), and corrosiveness (a) in the combustion test. The domestic GB31247 "Classification of Combustion Performance of Cables and Optical Cables" also divides the flame retardant performance of cables into four levels: A, B1, B2, and B3, based on multiple indicators such as combustion calorific value, flame spread, peak heat release rate, and smoke production rate index. In addition, on this basis, additional performance levels are identified based on three indicators in the combustion test: burning drips / particles (d), smoke toxicity level (t), and corrosiveness (a). Therefore, the research and development significance of zero-drip B1-level high flame retardant soft cables for communication power supplies is in line with the current international expectations for flame retardant cables.

[0003] The existing technologies all use highly flame-retardant sheath materials to reduce the combustible content of the materials, thereby reducing the total heat release and smoke release of the cable. However, this formula can only ensure that the heat release performance of the cable does not exceed the standard, but cannot ensure that the sheath or other structures will not fall off during combustion. Therefore, in the event of a fire, the burning and falling materials of the cable may ignite other items, causing the fire to expand. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the present invention provides a flame retardant sheath material which has good flame retardant effect and does not fall off during combustion.

[0005] In a first aspect, the present application provides a zero-drip flame-retardant sheath material, comprising the following components in weight percentage:

[0006]

[0007] The inorganic flame retardant includes aluminum hydroxide and magnesium hydroxide. In parts by weight, the magnesium hydroxide accounts for 10% to 40% of the total formula content, the aluminum hydroxide accounts for 10% to 40% of the total formula content, the compatibilizer is ethylene-methacrylic acid, the antioxidant is a hindered phenol antioxidant, and the carbon-forming agent is sepiolite.

[0008] More specifically, the silicone is in the form of solid silicone particles.

[0009] More specifically, the content of the carbon-forming agent is 2% to 4.5%.

[0010] More specifically, the content of the magnesium hydroxide is 15% to 25%, and the content of the aluminum hydroxide is 15% to 25%.

[0011] In a second aspect, the present application provides a method for preparing a zero-drip flame-retardant sheath material, comprising the following steps:

[0012] S1. Add EVA, POE, LLDPE, HDPE, compatibilizer, antioxidant, aluminum hydroxide, magnesium hydroxide, carbon black, silicone, EBS, TAIC, silicone oil and carbon-forming agent into a stirrer according to mass percentage and mix them evenly to obtain a sheath material mixture;

[0013] S2. The sheath material mixture is subjected to a mixing process, a plasticizing process and an extrusion granulation process in sequence to finally obtain the zero-drip flame-retardant sheath material.

[0014] More specifically, in the extrusion granulation process, the sheath material mixture passes through four temperature zones with increasing temperatures in the extruder, namely: zone one at 90°C, zone two at 110°C, zone three at 125°C, and zone four at 140°C.

[0015] In a third aspect, the present application provides a zero-drip flame-retardant flexible cable, wherein the outermost layer of the cable is a flame-retardant sheath made of the zero-drip flame-retardant sheath material.

[0016] More specifically, the cable comprises, from inside to outside, a cable conductor, an insulating layer wrapped around the conductor, a cable wrap and the flame retardant sheath, and a flame retardant filling material is provided between the insulating layer and the cable wrap.

[0017] More specifically, the flame retardant filling material is a flame retardant mineral material, and the flame retardant mineral material is selected from at least one of basalt, magnesium oxide, aluminum oxide, and silicon dioxide.

[0018] In a fourth aspect, the present application provides a method for preparing a zero-drip flame-retardant flexible cable, comprising the following steps:

[0019] T1. Use a wire drawing machine to draw the conductor wire into a conductor monofilament with a diameter of 0.15 mm to 0.39 mm, then use an annealing furnace to anneal the conductor monofilament into a conductor monofilament with a breaking elongation of ≥15%, and after the treatment, twist the conductor monofilament into strands to obtain a cable conductor;

[0020] T2. Use an extruder to evenly extrude the insulating material onto the outer surface of the stranded cable conductor;

[0021] T3, use the cabling and paralleling mold to fill the cable conductor with flame retardant filling material, and wrap the cable wire around the outermost layer;

[0022] T4. Use an extruder to extrude and melt the zero-drip flame-retardant sheath material, and then use an extrusion process to extrude it onto the cable wrap after it is shaped by an extrusion die to form a zero-drip flame-retardant soft cable.

[0023] The beneficial effects of the present invention are:

[0024] 1. The cable designed in this application uses a multi-filament twisted soft conductor and a flexible sheath inside, which increases the overall flexibility of the cable and allows the cable to be laid in a narrower place. The addition of flame retardants in traditional flame retardant sheaths greatly reduces their mechanical properties, and traditional flame retardant sheaths are more prone to cracking. In this application, by optimizing the proportion of components, the sheath has excellent flame retardant properties and can maintain good flexibility.

[0025] 2. This application uses a highly crusting polyolefin sheath material. The flame-retardant sheath made of it does not fall off when the open flame power is less than 22kW, avoiding the problem of the burning cable further igniting other items, and more effectively preventing the fire from spreading. Through formula design, the strength of the carbon shell formed by the sheath after the fire is also improved. The carbon shell can withstand slight vibrations and winds below 6m / s, avoiding the carbon shell from breaking or falling off under slight influences after burning, and avoiding the problem of the high-temperature carbon shell continuing to ignite other items.

[0026] 3. All materials in the cable designed in this application do not contain toxic substances such as arsenic or bromine compounds, which improves the safety of the cable to people and the environment; BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a structural schematic diagram of the zero-drip flame-retardant flexible cable in this application.

[0028] In the figure: 1. Cable conductor; 2. Insulation layer; 3. Flame retardant filling material; 4. Cable wrapping; 5. Flame retardant sheath. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the specific implementation methods of the present invention are clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the formula designed by the present invention, the main resin in the sheath material is composed of ethylene-vinyl acetate copolymer EVA, polyolefin elastomer POE, linear low-density polyethylene LLDPE and high-density polyethylene HDPE. In the main resin, with the help of compatibilizer ethylene-methacrylic acid and antioxidant hindered phenol type antioxidant BHA, the mixed inorganic flame retardant materials aluminum hydroxide and magnesium hydroxide are stabilized in the resin, the flame retardant and smoke suppression properties of the resin sheath material as a whole are enhanced, and the mechanical strength and low temperature tolerance of the material as a whole are maintained by adjusting the appropriate mass percentage. The added carbon black and carbonizing agent sepiolite further improve the flame retardancy of the product, reduce the heat release rate, total heat release and smoke production rate, so that the flame retardant sheath meets high standards in all aspects. The cable designed in this application meets the national B1 flame retardant requirements and has good mechanical properties, flame retardant properties and processing properties. Lubricant vinyl bis stearamide EBS, vulcanizing agent / cross-linking agent triallyl isocyanurate TAIC, and silicone oil are also added to the formula.

[0031] The added carbon-forming agent, sepiolite, is a naturally occurring hydrous magnesium silicate mineral, a type of clay mineral. It has a unique tubular structure consisting of alternating layers of silicon-oxygen tetrahedrons and magnesium-oxygen octahedrons. The chemical formula of sepiolite is: [(Mg,Al)5Si8O 20 (OH)2(OH2)·4H2O]. When the cable burns, the sepiolite itself acts as a skeleton and promotes the carbonization of the polymer resin. After burning, a dense carbon layer shell is formed. The carbon layer shell has a certain strength, which can ensure that the sheath does not drip after burning, and can effectively slow down or inhibit the expansion of combustion. In addition, the carbonized layer can also cut off the overflow of combustible gas, inhibit the further heating of the polymer resin, and hinder the combustible gas generated by the thermal decomposition of the polymer, thereby further improving the overall flame retardant effect.

[0032] The silicone added to the formula refers to an organic silicon compound containing a silicon-oxygen bond (Si-O). The silicone added in this application is solid silicone particles. In the flame retardant jacket material formula, silicone can improve the wear resistance of the polymer and extend the service life of the product; it can improve the flexibility and elasticity of the polymer so that it can maintain good performance even at low temperatures; it can improve the thermal stability of the polymer so that it can maintain performance even at high temperatures; it can improve the surface properties of the polymer, such as improving the surface smoothness and anti-stickiness of the molded jacket and reducing friction; it can also improve the UV resistance of the polymer and extend its service life in outdoor environments.

[0033] The silicone oil added to the formula is a type of low molecular weight linear polysiloxane, usually a colorless or light yellow transparent liquid, with excellent thermal stability and chemical stability, as well as good electrical insulation. In the flame retardant sheath material formula, silicone oil can be used as a lubricant for polymers to reduce the friction between polymers and other materials and improve their sliding properties; it can improve the flexibility of polymers so that they can maintain good performance even at low temperatures; it can improve the thermal stability of polymers so that they can maintain performance even at high temperatures; it can be used as a release agent for polymers to reduce the adhesion of polymers to the mold during the molding process and improve production efficiency; when polymers are blended with other materials, silicone oil can be used as a compatibilizer to further improve the compatibility of polymers with other materials. It can be used as a defoamer for polymers to reduce the generation of bubbles and improve product quality. It can be used as a softener for polymers to improve the softness and feel of polymers.

[0034] In some specific embodiments, EVA uses a product model of 7875S, POE uses a product model of 5054D, LLDPE uses a product model of 3210FB, HDPE uses a product model of 3461, and carbon black uses a product model of XP-983.

[0035] The present application provides a method for preparing a flame retardant sheath material:

[0036] S1. Add EVA, POE, LLDPE, HDPE, compatibilizer, antioxidant, aluminum hydroxide, magnesium hydroxide, carbon black, silicone, EBS, TAIC, silicone oil and carbon-forming agent into a blender according to mass percentage, mix thoroughly until uniform, and form a mixed substance.

[0037] S2, the mixed material obtained in step S1 is sequentially subjected to a mixing process, a plasticizing process and an extrusion granulation process to obtain a flame retardant sheath material. Preferably, a low compression ratio screw extruder with an L / D ratio of not less than 20 and a compression ratio of 1:1.2 is used for extrusion granulation, and the extrusion temperatures of each section in the extruder are: 90°C in zone 1, 110°C in zone 2, 125°C in zone 3, 140°C in zone 4, 145°C in die head and 145°C in die head.

[0038] According to the above method, the specific embodiments and their performance test results are listed below.

[0039] Embodiment 1:

[0040] In terms of weight percentage, the following are EVA 28%, POE 5%, LLDPE 12%, HDPE 3%, compatibilizer 2%, antioxidant 0.1%, aluminum hydroxide 20%, magnesium hydroxide 22%, carbon black XP-983 0.5%, silicone 1%, EBS 0.8%, TAIC 0.2%, silicone oil 157 1%, and carbonizing agent 4.4%.

[0041] Embodiment 2:

[0042] In terms of weight percentage, the following ingredients are used: EVA 30%, POE 3%, LLDPE 10%, HDPE 10%, compatibilizer 2%, antioxidant 0.1%, aluminum hydroxide 20%, magnesium hydroxide 20%, carbon black XP-983 0.8%, silicone 1%, EBS 0.5%, TAIC 0.3%, silicone oil 157 0.3%, and carbonizing agent 2.0%.

[0043] Comparative Example 1:

[0044] In terms of weight percentage, the following are EVA 35%, POE 7%, LLDPE 10%, HDPE 5%, compatibilizer 2%, antioxidant 0.1%, aluminum hydroxide 15%, magnesium hydroxide 20%, carbon black XP-983 0.8%, silicone 1%, EBS 0.5%, TAIC 0.6%, silicone oil 157 0.6%, and carbonizing agent 2.4%.

[0045] The sheath material components of Examples 1, 2 and Comparative Example 1 were respectively prepared into flame-retardant sheaths according to the above method, and elongation at break test, tensile strength test and residual carbon shell strength test after combustion were respectively carried out, and the performance test results are shown in the following table:

[0046] Elongation at break (%) Tensile strength(Mpa) Carbon shell strength(Mpa) Example 1 184 10.8 4.8 Example 2 192 11.5 3.4 Comparative Example 1 198 12.1 0.7

[0047] It can be seen from the above performance test results that in Examples 1 and 2, the flame retardant sheath prepared according to the formula designed in this application has excellent elongation at break and high tensile strength, is relatively soft, has good toughness, and can adapt to the external environment. The main components of the carbon shell remaining after the flame retardant sheath is a shell formed by inorganic flame retardant materials magnesium hydroxide, aluminum hydroxide and carbon-forming agent sepiolite. The residual carbon shell in Examples 1 and 2 has high strength and is not easily blown off by natural wind. In Comparative Example 1, the content of resin EVA as the main combustion product is high, resulting in a larger proportion of combustible components in the outer sheath. After combustion, the carbon shell is unstable, the carbon shell has low strength, and is easy to break, and more dripping occurs during the combustion process.

[0048] The present application provides a zero-drip flame-retardant flexible cable, which includes, from the inside to the outside, a cable conductor, an insulating layer wrapped around the outside of the conductor, a cable wrap, and a flame-retardant sheath, and a flame-retardant filling material is provided between the insulating layer and the cable wrap. The flame-retardant filling material is a flame-retardant mineral material, and the flame-retardant mineral material is selected from at least one of basalt, magnesium oxide, aluminum oxide, and silicon dioxide.

[0049] The present application provides a method for preparing a zero-drip flame-retardant flexible cable, comprising the following steps:

[0050] T1. Use a wire drawing machine to gradually stretch the Ф1.2mm copper rod conductor wire into a conductor monofilament with a diameter of 0.15mm to 0.39mm. Then use a high-temperature annealing furnace at 580℃ to 600℃ to anneal the conductor monofilament. During the annealing process, the broken lattice caused by wire drawing in the conductor monofilament can be reassembled and arranged. After annealing, the elongation at break of the conductor monofilament is ≥15%. After treatment, the conductor monofilaments are twisted into strands in the manner of (1+6+12+18) to obtain a cable conductor. This twisting process can ensure that the twisted conductor has good softness and large bendability. The structure is stable when the wire core is bent, and the plastic deformation of the conductor will not be caused. The softness and stability of the wire core are greatly improved, which is convenient for the processing, manufacturing, installation and laying of wires and cables. It can also avoid the problem of single wire breakage and puncturing the insulation layer when the cable is bent at a small angle.

[0051] T2. Use an extruder to evenly extrude the low-smoke halogen-free polyolefin insulation material onto the outer surface of the stranded cable conductor, wherein the oxygen index of the low-smoke halogen-free polyolefin is ≥30%.

[0052] T3, use the cabling and paralleling mold to fill the flame retardant filling material outside the cable conductor, and wrap the cable around the outermost layer. The wrapping uses a silicone mica composite tape, which is made of 0.08mm thick phlogopite, 0.02 thick silicone layer, and 50MPa glass fiber base cloth. When wrapping, the mica is on the outermost layer, because the dense mica layer can completely resist the invasion of flames and can further protect the internal wires. The middle is the silicone layer. The silicone can form a tubular protective shell after heating. The protective shell can play a role in heat insulation and ensure that the internal temperature of the cable core is much lower than the external temperature. The glass fiber base cloth is in the innermost layer. Because the glass fiber cloth is strong, it can prevent the deformation of the cable core caused by the expansion of the internal material after heating, which can prevent the sheath from being damaged by internal stress after the shell is formed.

[0053] T4. Use an extruder to extrude and melt the zero-drip flame-retardant sheath material, and then use an extrusion process to extrude it onto the cable wrap after it is shaped by an extrusion die. The extrusion process can expel the air between the cable core and the sheath, so that the sheath material is more tightly wrapped around the cable core to form a zero-drip flame-retardant soft cable.

[0054] The zero-drop flame-retardant soft cable prepared by the above method has been subjected to a combustion test. The outer sheath of the cable can form a carbon shell when it encounters an open flame and high temperature within a power of less than 22kW. The carbon shell does not powder, break or fall off when the wind speed is ≤6m / s. The carbon shell strength is ≥4MPa, which can be lower than the slightly vibrating wind or heat wave, ensuring that the carbon shell has a certain stress resistance under continuous flame conditions, and can effectively prevent the expansion of the combustion range. The outermost flame-retardant sheath of the cable has an elongation at break of ≥180%, and a tensile strength of ≥10.5MPa. The material has good softness, which can improve the overall softness of the cable, so that the minimum bending radius of the cable is ≥8 times the outer diameter of the cable, and can be used in various laying environments.

[0055] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A zero-drip flame-retardant sheath material, characterized in that: The following components are included in weight percentage: The inorganic flame retardant includes aluminum hydroxide and magnesium hydroxide. In parts by weight, the magnesium hydroxide accounts for 10% to 40% of the total formula content, the aluminum hydroxide accounts for 10% to 40% of the total formula content, the compatibilizer is ethylene-methacrylic acid, the antioxidant is a hindered phenol antioxidant, and the carbon-forming agent is sepiolite.

2. The zero-drip flame-retardant sheath material according to claim 1, characterized in that: The silicone is in the form of solid silicone particles.

3. The zero-drip flame-retardant sheath material according to claim 1, characterized in that: The content of the carbon-forming agent is 2% to 4.5%.

4. The zero-drip flame-retardant sheath material according to claim 1, characterized in that: The content of the magnesium hydroxide is 15% to 25%, and the content of the aluminum hydroxide is 15% to 25%.

5. A method for preparing the zero-drip flame-retardant sheath material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Add EVA, POE, LLDPE, HDPE, compatibilizer, antioxidant, aluminum hydroxide, magnesium hydroxide, carbon black, silicone, EBS, TAIC, silicone oil and carbon-forming agent into a stirrer and mix them evenly to obtain a sheath material mixture; S2. The sheath material mixture is subjected to a mixing process, a plasticizing process and an extrusion granulation process in sequence to finally obtain the zero-drip flame-retardant sheath material.

6. The preparation method according to claim 5, characterized in that: In the extrusion granulation process, the sheath material mixture passes through four temperature zones with increasing temperatures in the extruder, namely: zone one at 90°C, zone two at 110°C, zone three at 125°C, and zone four at 140°C.

7. A zero-drip flame-retardant flexible cable, characterized in that: The outermost layer of the cable is a flame-retardant sheath made of the zero-drip flame-retardant sheath material according to any one of claims 1 to 4.

8. The zero-drip flame-retardant flexible cable according to claim 7, characterized in that: The cable comprises, from the inside to the outside, a cable conductor, an insulating layer wrapped around the cable conductor, a cable wrap and the flame-retardant sheath, and a flame-retardant filling material is provided between the insulating layer and the cable wrap.

9. The zero-drip flame-retardant flexible cable according to claim 8, characterized in that: The flame retardant filling material is a flame retardant mineral material, and the flame retardant mineral material is selected from at least one of basalt, magnesium oxide, aluminum oxide, and silicon dioxide.

10. A method for preparing the zero-drip flame-retardant flexible cable according to any one of claims 8 to 9, characterized in that: The following steps are involved: T1. Use a wire drawing machine to draw the conductor wire into a conductor monofilament with a diameter of 0.15 mm to 0.39 mm, then use an annealing furnace to anneal the conductor monofilament into a conductor monofilament with a breaking elongation of ≥15%, and after the treatment, twist the conductor monofilament into strands to obtain a cable conductor; T2. Use an extruder to evenly extrude the insulating material onto the outer surface of the stranded cable conductor; T3, use the cabling and paralleling mold to fill the cable conductor with flame retardant filling material, and wrap the cable wire around the outermost layer; T4. Use an extruder to extrude and melt the zero-drip flame-retardant sheath material, and then use an extrusion process to extrude it onto the cable wrap after it is shaped by an extrusion die to form a zero-drip flame-retardant soft cable.

Citation Information

Cited By

  • Zero-dripping flame-retardant flexible cable and preparation method therefor

    WO2026061111A1